Millennium Shop Information System - Anisa Julva; Dewi Novita; Dwiki Restu Aji; Melinda Dea; Riyan Abdul (Formosa Journal of Applied Sciences, 2023)
Toko Millennium Shop is a shop that runs a business in the electronics sector which is domiciled in Solo, Central Java. Currently the Millennium Shop wants to improve service and work efficiency in terms of time and energy. This is done because as the shop develops, the current business processes cause problems such as a lack of work efficiency in terms of time and energy. This happens because of poor management and archiving of sales transaction data, goods management. On the other hand, poor sales data archiving creates problems with financial records, sometimes there are some sales that are not recorded, so it is not known exactly how much income and expenses each month are from the existing archives.